FREQUENCY OF VARIOUS OCULAR PATHOLOGIES DETECTED ON B-SCAN ULTRASONOGRAPHY IN PATIENTS OF BLUNT OCULAR TRAUMA - ALI , M; AAQIL , B; NAZNEEN , Z; ZEB , A; HAFEEZ , QZ; KHAN, AA (Biological and Clinical Sciences Research Journal, 2024)
Ultrasound (USG) B-Scan is a readily available, rapid, non-invasive and safe imaging modality to evaluate the clinical findings of traumatic eyes. Ultrasound B Scan is based on the 'Piezoelectric' phenomenon by using a frequency that lies in the range from 5MHz to 20MHz. Ultrasound B Scan can detect, outline and characterize the nature of soft tissue of the eyeball and orbit, regardless of the degree of ocular media transparency. Objective: To determine the frequency of various ocular pathologies detected on B-scan ultrasonography in patients of blunt ocular trauma. Methods: This cross-sectional study was conducted from 8th November 2022 to 7th May 2023 at Ayub Teaching Hospital Abbottabad. The study enrolled 127 patients with blunt ocular trauma between 15 to 65 years of age Patients with any known post-segment pathology before ocular trauma and patients with a history of diabetes and hypertension were excluded. Then gentle B scan was performed. The eye was anaesthetized using a topical anaesthetic. Gel was applied to the closed eye. A transverse probe position was used. Each quadrant of the eye was examined using the limbus to fornix approach. The 12- O'clock, 3-O'clock, 6-O'clock, and 9-O'clock positions were examined carefully. Ocular pathologies like vitreous haemorrhage, retinal detachment, intraocular foreign body and endophthalmitis (yes/no) were noted. Results: In our study, the frequency of various ocular pathologies detected on B-scan ultrasonography in patients of blunt ocular trauma were as follows; Vitreous haemorrhage was most common and seen in 49 (38.58%) patients followed by Retinal detachment in 28 (22.05%) patients, Intra-ocular foreign bodies were seen in 15 (11.81%) patients and endophthalmitis in 14 (11.02%) patients. Conclusion: This study concluded that the vitreous hemorrhage was the most common pathology in ocular trauma followed by retinal detachment and intra-ocular foreign bodies.